Winner's curse and bandwagon effect in Malaysian IPOs: evidence from 2001-2009 - Othman Yong (Penerbit Universiti Kebangsaan Malaysia, 2011)
This papaer examines the winner's curse hypothesis and the bandwagon effect in initial public offerings (IPOS), using malaysian IPO data from January 2001 to December 2009. The average initial return (offer-to-close) for the 160 Malaysian private placement IPOS is 18.51 percent as opposed to the average initial return (offer-to-lose) of 28.84 percent for the 210 non-private placement IPOS, which gives support to the winner's curse hypothesis , where uninformed investors (using private placement IPOS as the proxy) demand a higher initial return in the absense of informed investors (using private placement IPOS as the proxy).The study also finds that the present of a large number of informed investors in an IPO exercise, as compared to uninformed investors, brings with it an increased interest, or the bandwagon effect, in that particular stock, which results in higher initial return.